2012
DOI: 10.1128/aem.06537-11
|View full text |Cite
|
Sign up to set email alerts
|

Dead or Alive: Deformed Wing Virus and Varroa destructor Reduce the Life Span of Winter Honeybees

Abstract: Elevated winter losses of managed honeybee colonies are a major concern, but the underlying mechanisms remain controversial. Among the suspects are the parasitic mite Varroa destructor, the microsporidian Nosema ceranae, and associated viruses. Here we hypothesize that pathogens reduce the life expectancy of winter bees, thereby constituting a proximate mechanism for colony losses. A monitoring of colonies was performed over 6 months in Switzerland from summer 2007 to winter 2007/2008. Individual dead workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
281
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(303 citation statements)
references
References 58 publications
16
281
4
2
Order By: Relevance
“…These results are in contrast to other studies around the world where Varroa mites played a significant or central role in colony losses (Bailey and Ball, 1991;Brodschneider et al, 2010;Dainat et al, 2012b;Dietemann et al, 2012;Guzman-Novoa et al, 2010;Ritter, 1981;Rosenkranz et al, 2010;Schäfer et al, 2010;Shimanuki et al, 1994). Also, the close association between Varroa mites and viruses (especially DWV, ABPV) and the subsequent colony losses they usually cause (Berthoud et al, 2010;Dainat et al, 2012a;Martin et al, 2012) were not observed in this study. Even though some apiaries in this study were occasionally infested with multiple pathogens and parasites, no obvious signs of disease were observed; thereby suggesting that the savannah honeybee population studied is resistant to these assaults.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…These results are in contrast to other studies around the world where Varroa mites played a significant or central role in colony losses (Bailey and Ball, 1991;Brodschneider et al, 2010;Dainat et al, 2012b;Dietemann et al, 2012;Guzman-Novoa et al, 2010;Ritter, 1981;Rosenkranz et al, 2010;Schäfer et al, 2010;Shimanuki et al, 1994). Also, the close association between Varroa mites and viruses (especially DWV, ABPV) and the subsequent colony losses they usually cause (Berthoud et al, 2010;Dainat et al, 2012a;Martin et al, 2012) were not observed in this study. Even though some apiaries in this study were occasionally infested with multiple pathogens and parasites, no obvious signs of disease were observed; thereby suggesting that the savannah honeybee population studied is resistant to these assaults.…”
Section: Discussioncontrasting
confidence: 66%
“…The absence of DWV from the honeybee and Varroa mite samples collected during this study was unexpected given its high prevalence in apiaries around the world (Allen and Ball, 1996;Baker and Schroeder, 2008;Berényi et al, 2006;Chen and Siede, 2007;Ellis and Munn, 2005;Martin et al, 1998;Tentcheva et al, 2004a) and the close association of DWV with Varroa mites (Bailey and Ball, 1991;Bowen-Walker et al, 1999;Dainat et al, 2012a;Gisder et al, 2009;Martin et al, 2012;Yang and CoxFoster, 2005;Yue and Genersch, 2005). Recently, DWV was also found to be absent from wild A. m. scutellata drones collected in a South African Nature Reserve and honeybee samples from Uganda (Kajobe et al, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…Mortality can be driven by a number of interacting factors, including the parasitic mite Varroa destructor , other parasites and diseases, nutrition, pesticides, and socioeconomic factors (Berthoud et al 2010;Dainat et al 2012a;Dainat et al 2012b;Ellis et al 2010;Le Conte et al 2010;Potts et al 2010a;vanEngelsdorp and Meixner 2010). From 1947 to 2008, the total US honey bee population has declined by 61 % vanEngelsdorp and Meixner 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, BQCV and DWV are the two most common and prevalent virus infections in A. mellifera worldwide (Zhang et al, 2012). In addition, DWV has been associated with honeybee colony losses, especially in overwintering mortalities in some places in the world (Highfield et al, 2009;McMenamin and Genersch, 2015) and DWV is known to be a lethal pathogen for honeybees when it occurs at high loads in association with the ectoparasite Varroa destructor (Dainat et al, 2012). BQCV mainly affects developing queen larvae and pupae in the capped-cell stage causing the death of future queen bees (Chen and Siede, 2007;McMenamin and Genersch, 2015).…”
Section: Resultsmentioning
confidence: 99%